Prevalence Comparsion between typhoid fever and H. pylori bacteria in Al-Diwaniyah province - jaafer douhan, mujj; Khadeeja Abees Hmood (Al-Qadisiyah Journal of Pure Science, 2021)
Salmonella,H.pylori